2019
DOI: 10.2215/cjn.04100318
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model for Severe AKI in Critically Ill Adults That Incorporates Clinical and Biomarker Data

Abstract: Background and objectivesCritically ill patients with worsening AKI are at high risk for poor outcomes. Predicting which patients will experience progression of AKI remains elusive. We sought to develop and validate a risk model for predicting severe AKI within 72 hours after intensive care unit admission.Design, setting, participants, & measurementsWe applied least absolute shrinkage and selection operator regression methodology to two prospectively enrolled, critically ill cohorts of patients who met cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…Newer developments related to monitoring and evaluating risk progression include e-alert systems, machine-learning algorithms and artificial intelligence for AKI recognition and monitoring, 20,[33][34][35][36] as well as models based upon the renal angina index, 37,38 furosemide stress test (FST), 39 or biomarkers. [40][41][42][43] In revisiting the guideline for AKI, severity of AKI should be based not only upon serum creatinine elevation and urine output, but also upon duration, possibly with the inclusion of biomarkers. The need to increase attention for persistent (>48 hours) AKI should also be considered.…”
Section: Determining Cause and Prognosismentioning
confidence: 99%
“…Newer developments related to monitoring and evaluating risk progression include e-alert systems, machine-learning algorithms and artificial intelligence for AKI recognition and monitoring, 20,[33][34][35][36] as well as models based upon the renal angina index, 37,38 furosemide stress test (FST), 39 or biomarkers. [40][41][42][43] In revisiting the guideline for AKI, severity of AKI should be based not only upon serum creatinine elevation and urine output, but also upon duration, possibly with the inclusion of biomarkers. The need to increase attention for persistent (>48 hours) AKI should also be considered.…”
Section: Determining Cause and Prognosismentioning
confidence: 99%
“…Although the study had limitations regarding AKI risk prediction, as their main goal was to incorporate new urinary markers as risk factors, the study showed that the inclusion of novel biomarkers could improve the robustness of a prediction model in early periods of critical care. Although there is no consensus regarding using such biomarkers to predict AKI, several have shown promising results [37,53,[78][79][80]. Therefore, a novel biomarker that directly reflects kidney injury may further improve prediction in the future.…”
Section: The Important Role Of Noble Biomarkers In Aki Prediction Modelsmentioning
confidence: 99%
“…Recently, Bhatraju et al developed a three variable model to predict severe AKI which performed excellent in a group of 1075 SIRS patients . This model yielded a much higher AUROC compared to our model, possibly explained by differences in AKI stage, and outcome definition.…”
Section: Discussionmentioning
confidence: 59%
“…This model yielded a much higher AUROC compared to our model, possibly explained by differences in AKI stage, and outcome definition. Moreover, the model was developed and validated internally in a highly selected population and includes a biomarker, which may not be available everywhere …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation